RANCANG BANGUN SISTEM MONITORING KUALITAS UDARA PADA RUANG ISOLASI COVID-19 BERBASIS ANDROID MENGGUNAKAN SENSOR SHARP GP2Y1010AU0F - Wahyu Siti Ulam Sari; Gigih Priyandoko; Dedi Usman Effendy (JASEE Journal of Application and Science on Electrical Engineering, 2022)
The combination of particles and gases with a specific concentration will be an air pollution that is dangerous for life. So air quality openly places and public health service institutions are also affected. One of them is a hospital is a place of health services for the surrounding community must have an inpatient room that is qualified both air conditioning, construction, waste treatment and facilities. Air conditioning systems are very important, especially in isolation rooms to prevent the breeding and proliferation of COVID-19. This research aims to find out the air quality in the isolation room has met existing standards or not, it requires monitoring of temperature, humidity and air pollution by harmful gases periodically and in real time. In addition, it makes it easier for officers in the monitoring room to know the air quality at any time and can save time and improve air conditioning monitoring so that it is more efficient. The results showed that the room using air conditioners can adequately standardize air quality for COVID-19 isolation rooms. The results of the experiment were a temperature of 24°C, humidity of 64.1%, carbon dioxide of 0.07ppm, carbon monoxide of 26.74 μg/m3, and air particulates of 0 μg/m3. This thesis is expected to contribute to increasing the number of COVID-19 declines and realizing the prototype of the air quality monitoring system design in the COVID-19 isolation room.